Organic Light Emitting Devices - Singh, Jai (IntechOpen, 2012)
This book describes the state-of-the-art advancement in the field of organic electroluminescence contributed by many researchers with internationally established expertise in the field. It includes original contributions on the synthesis of suitable organic materials, fabrication of organic light emitting devices (OLEDs) and organic white light emitting devices (WOLEDs), characterization of these devices and some designs for optimal performance. All chapters are self-sufficient in presenting their contents. The cost effective chemical technology offers many exciting possibilities for OLEDs and organic solar cells (OSCs) to be futuristic solutions for lighting and power generation. A common flexible substrate can be used to fabricate OLEDs on one side facing a room and OSCs on the other side facing the sun. The device thus fabricated can generate power in the day time and light a room/house at night. The book covers developments on OLEDs, WOLEDs and briefly on OSCs as well.